PARITIES, HISTORY OF HYPERTENSION, AND BODY INDEX OF HYPERTENSION IN PREGNANCY - Sekarini, Ni Nyoman Ayu Desy; Espana Giri, Ketut (Jurnal Kesehatan Al-Irsyad, 2021)
The increase in blood pressure during pregnancy is physiological, but about 12-22% of this increase leads to an abnormal pregnancy and 17% leads to death in the mother. The impact of hypertension in pregnancy is maternal and neonatal impacts. Maternal impacts arising from hypertension in pregnancy include maternal mortality with PEB in the form of mortality, HELLP syndrome, visual disturbances, eclampsia, ICU care, and sepsis, while perinatal outcomes include perinatal mortality, IUGR, LBW, asphyxia, fetal distress, and premature. The research design was non-reactive research with a case control approach using a sample group of 37 respondents and a control group of 127 respondents (total 164 respondents). The type of data is secondary data obtained from medical records. The data scale is nominal so that the analysis uses the chi-square test. The results showed that 22.6% had hypertension in pregnancy, 69.5% were multigravidas, 76.2% had no family history of hypertension, 81.7% had no history of hypertension, and 57.9% had BMI <25. The results of the analysis showed that there was a relationship between parity, family history of hypertension, family history, and BMI with the incidence of hypertension in pregnancy. Furthermore, a further test was carried out, the results showed that the parity variable was the dominant factor that had an influence on the incidence of hypertension in pregnancy with an OR -2.421, 95% CI, which means that primigravidas have a risk of 2.421 times lower than multigravidas.